2019
DOI: 10.1016/j.jcp.2019.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Ray effect mitigation for the discrete ordinates method through quadrature rotation

Abstract: Solving the radiation transport equation is a challenging task, due to the high dimensionality of the solution's phase space. The commonly used discrete ordinates (S N ) method suffers from ray effects which result from a break in rotational symmetry from the finite set of directions chosen by S N . The spherical harmonics (P N ) equations, on the other hand, preserve rotational symmetry, but can produce negative particle densities. The discrete ordinates (S N ) method, in turn, by construction ensures non-neg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Similar discussions can be found in radiative transfer in the discretization of angular variables [15]. In addition, the mitigation methods which are equivalent to obtaining the solutions with more discrete velocities can be employed as well, such as taking averaged solutions over multiple times of computations on different sets of velocity space discretization [11][12][13].…”
Section: Mitigation Solutionsmentioning
confidence: 85%
See 1 more Smart Citation
“…Similar discussions can be found in radiative transfer in the discretization of angular variables [15]. In addition, the mitigation methods which are equivalent to obtaining the solutions with more discrete velocities can be employed as well, such as taking averaged solutions over multiple times of computations on different sets of velocity space discretization [11][12][13].…”
Section: Mitigation Solutionsmentioning
confidence: 85%
“…However, for the standard quadrature sets of DOM, undesirable negative weights will occur for N > 12, which gives an upper limit on the number of angular directions and constrains the S N method to fully remove the ray effect. Therefore, many strategies have been proposed to adjust the angular discretization and quadrature sets in order to mitigate the ray effect, such as T N quadrature set [10], staggered and adaptive quadrature sets [11], and quadrature rotation [12,13]. Detailed analysis and reviews can be found in [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…This is a particularly difficult problem for the S n based methods because they suffer from severe ray effect. Previous studies have used this problem for comparisons between methods [38] and as a test case for schemes to mitigate the ray effect [39]. Both the UGKWP method and the Monte Carlo method use 201 × 201 cells in space.…”
Section: Line-source Problem In Purely Scattering Homogeneous Mediummentioning
confidence: 99%
“…In terms of ray effects, in addition to increase discrete directions, to modify direction layout is another common remedy [11][12][13][14][15]. Numerical experiments have been conducted by Li et al [11] showing that ray effects can be reduced by modifying direction layouts, and three corresponding countermeasures were proposed in their paper.…”
Section: Introductionmentioning
confidence: 99%
“…Tencer [12] proposed a ray effects mitigation technique by averaging the computed results of various direction layouts, which are generated by arbitrarily rotating the reference layout. Quadrature rotation was also applied to solve time-dependent transport and results showed that ray effects were reduced significantly, including for small numbers of quadrature points [13]. Recently, goal-oriented angular adaptive algorithm was also utilized to mitigate ray effects [14,15].…”
Section: Introductionmentioning
confidence: 99%